A dimensional analysis to quantify the thermal budget around lithospheric‐scale shear zones. (7th April 2015) - Duprat‐Oualid, Sylvia; Yamato, Philippe; Schmalholz, Stefan M.
Abstract The thermal evolution around shear zones is controlled by three major thermal processes: diffusion, advection and shear heating. We present a dimensional analysis to quantify, to first‐order, the relative contributions of these three processes to the thermal evolution around lithospheric‐scale shear zones. We consider 11 parameters that control the kinematics, the three‐dimensional (3‐D) geometry, the initial thermal structure and the average strength of the shear zone. Three dimensionless parameters are presented to quantify the relative contributions of the three thermal processes. We validate the dimensional analysis with 2‐D thermo‐kinematic numerical models. The applicability of the dimensional analysis to any kind of shear zone (i.e. thrust, normal‐slip and strike‐slip shear zones) makes it a useful tool that is complementary to previous numerical and analytical studies. Finally, thrust‐type shear zones are used to illustrate how the three thermal processes control the thermal evolution.